USING SPACE SYNTAX TO DETERMINE THE FORM AND PATTERN OF HERITAGE SITE (Case Study: Sangiran Heritage Site) - Mila Karmila; Nyandra Sari Magfiroh (Universitas Islam Sultan Agung Semarang, 2018)
ABSTRACTThere are 10 criteria of world heritage sites that have been set by UNESSCO. The category is divided into two categories of cultural sites and natural sites. Area of Ancient Human Site in Sangiran is included in the category of cultural sites. Sangiran region has begun to develop since 2005. In 2012 the government to plan and develop on a large scale so that now the region currently has 5 museums with international standard. From this activity began to appear very significant changes to the region Sangiran. The growth of trade, settlements, tourism and service has influenced regional shape and form.To know the changes that occur in the region of Sangiran the studied used space syntax analysis method, which in its approach using a quantitative approach. The space syntax analysis method will be adjusted with the steps of configuration method. The analysis variables used are the characteristics of the region, the anatomy of the region and the blueprint of the expanse. Using various indicators such as scarcity, historicity and scientific value, and the road net. In conformity with the variables and indexes that have been brought up, is expected to produce research output in accordance with the title, the Form and Pattern of Ancient Site Site Sangiran, Sragen regency. The result of this study shows that Sangiran area tends to be fragmented cities, with space syntax R2 value of 0.012714 (intelligibility value). In addition, based on the pattern of development of the Sangiran region in the form of dispersing pattern. This is due to the development of homogeneous economic activities and parallel to the road network.Keywords : space syntax, determine, form and pattern, heritage site ABSTRAK Terdapat 10 kriteria situs warisan dunia yang telah di tetapkan oleh UNESSCO dan dikatagorikan menjadi dua bagian yaitu katagori situs budaya dan situs alam. Kawasan Situs Manusia Purba yang ada di Sangiran ini termasuk dalam katagori situs budaya. Kawasan Sangiran mulai berkembang pada tahun 2005 kawasan ini hanya berdiri satu bangunan berbentuk joglo sehingga tidak berdampak besar di sekitar kawasan. Pada 2012 pemerintah melakukan perencanaan dan pembangunan secara besar-besaran sehingga sekarang kawasan heritage ini telah memiliki 5 museum berstandar internasional. Dari kegiatan tersebut terjadi perubahan yang sangat signifikan terhadap kawasan pariwisata, permukiman, perdagangan dan jasa yang berpengaruh terhadap bentuk dan pola kawasan.Untuk mengetahui adanya perubahan di kawasan Sangiran, digunakan pendekatan kualitatif dengan metode space syntax. Metode ini akan menggunakan analisis space syntax dan disesuaikan dengan langkah-langkah metode konfigurasi. Variabel analisis yang digunakan adalah karakteristik wilayah, anatomi wilayah dan cetak biru hamparan. Menggunakan berbagai indikator seperti kelangkaan, historisitas dan nilai ilmiah, dan jaring jalan. Sesuai dengan variabel dan indeks yang telah dikemukakan, diharapkan dapat menghasilkan output penelitian sesuai dengan judul, Bentuk dan Pola Situs Situs Kuno Sangiran, Kabupaten Sragen. Hasil dari penelitian ini menunjukkan bahwa daerah Sangiran cenderung menjadi kota yang terfragmentasi, dengan nilai R2 sintaksis ruang 0,012714 (nilai kejelasan). Selain itu, berdasarkan pola perkembangan wilayah Sangiran dalam bentuk pola pendispersi. Hal ini disebabkan perkembangan kegiatan ekonomi yang homogen dan sejajar dengan jaringan jalan.Keywords : space syntax, determine, form and pattern, heritage site